Testosterone Therapy Effects on Bone Mass and Turnover in Hypogonadal Men with Type 2 Diabetes - Colleluori, Georgia; Aguirre, Lina; Napoli, Nicola; Qualls, Clifford; Villareal, Dennis T; Armamento-Villareal, Reina (The journal of clinical endocrinology and metabolism, 2021)
Abstract Context Male hypogonadism is associated with low bone mineral density (BMD) and increased fragility fracture risk. Patients with type 2 diabetes (T2D) have relatively higher BMD, but greater fracture risk. Objective Evaluate the skeletal response to testosterone therapy in hypogonadal men with T2D compared with hypogonadal men without T2D. Methods Single arm, open-label clinical trial (NCT01378299) involving 105 men (40-74 years old), with average morning testosterone <300 ng/dL. Subjects were injected intramuscularly with testosterone cypionate (200 mg) every 2 weeks for 18 months. Testosterone and estradiol were assessed by liquid chromatography/mass spectrometry; serum C-terminal telopeptide of type I collagen (CTX), osteocalcin and sclerostin by enzyme-linked immunosorbent assay; glycated hemoglobin (HbA1c) by high-performance liquid chromatography, areal BMD (aBMD) and body composition by dual-energy x-ray absorptiometry; tibial volumetric BMD (vBMD) and bone geometry by peripheral quantitative computed tomography. Results Among our population of hypogonadal men, 49 had T2D and 56 were non-T2D. After 18 months of testosterone therapy, there were no differences in circulating testosterone and estradiol between the groups. Hypogonadal men with T2D had increased osteocalcin, reflecting increased osteoblast activity, compared with non-T2D men (P < .01). T2D men increased lumbar spine aBMD (P < .05), total area at 38% tibia (P < .01) and periosteal and endosteal circumferences at the same site (P < .01 for both). T2D men had reduced tibial vBMD (P < .01), but preserved bone mineral content (P = .01). Changes in HbA1c or body composition were similar between the 2 groups. Conclusion Testosterone therapy results in greater improvements in the skeletal health of hypogonadal men with T2D than their nondiabetic counterparts.